2012
DOI: 10.1002/chem.201200956
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Fused‐Ring‐Expanded Porphyrins that were Core‐Modified with Group 16 Heteroatoms

Abstract: The synthesis of a series of novel core-modified and fused-ring-expanded tetraphenylporphyrins is reported. Theoretical calculations and magnetic circular dichroism (MCD) and fluorescence spectroscopic measurements were used to analyze the effect of core modification with Group 16 oxygen, sulfur, selenium, and tellurium atoms on the optical properties and electronic structures of the porphyrins. Marked redshifts of the Q and B bands and accelerated intersystem-crossing rates were observed, thus making these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 104 publications
2
23
0
Order By: Relevance
“…The trends in the MO energies of the frontier π -MOs and in the HOMO-LUMO gaps of the analogous set of fused-ring-expanded phthalonitriles (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), shown in Figure 7, are also broadly similar to those predicted for the corresponding Pc (1-22) and aza-BODIPY (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) analogues. The alignments of the nodal planes of the a and s MOs (Figure 8) are similar to those of the corresponding tetraazapophyrin analogues (Figure 3), as would be anticipated based on their radial symmetry and the manner in which the 4 angular nodal planes lie on alternating sets of 8 atoms on the inner perimeter due to the M L = ± 4 properties.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The trends in the MO energies of the frontier π -MOs and in the HOMO-LUMO gaps of the analogous set of fused-ring-expanded phthalonitriles (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), shown in Figure 7, are also broadly similar to those predicted for the corresponding Pc (1-22) and aza-BODIPY (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) analogues. The alignments of the nodal planes of the a and s MOs (Figure 8) are similar to those of the corresponding tetraazapophyrin analogues (Figure 3), as would be anticipated based on their radial symmetry and the manner in which the 4 angular nodal planes lie on alternating sets of 8 atoms on the inner perimeter due to the M L = ± 4 properties.…”
Section: Resultssupporting
confidence: 68%
“…Although radially symmetric fused-ring-expansion with benzene rings is problematic from the standpoint of compound stability, there is scope for forming fused-ring-expanded Pc analogues with other types of peripheral fused rings. Recent research by Shen and Mack and coworkers 25,26 has pointed the way to a possible solution based on using other types of fused ring systems such as phenanthrenes, since the alignment of the nodal planes on the peripheral fused rings differ markedly from those of benzo-fused analogues (Figure 3). In the context of porphyrin analogues, 24−26 the incorporation of phenanthrene moieties has been shown to result in significant red shifts of the main spectral bands due to a stabilization of the LUMO rather than a destabilization of the HOMO.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 They successfully synthesized coremodified porphyrin 39 by the condensation reaction of pyrrole 19 and thiophenediol using the Ulman method 15 in 18% yield (Scheme 4). 32 The incorporation of phenanthrene fused pyrrole efficiently extended the p-conjugation of porphyrin and redshifted its Soret and Q bands to 514 and 837 nm in CHCl 3 , respectively. Moreover, the emission band of 39 centered at l 4 900 nm.…”
Section: Porphyrinoids Embedded With Type I Building Blocksmentioning
confidence: 99%
“…As shown in Scheme 5, Shen et al reported the reaction of lithium salt of 40 with p-fluorobenzaldehyde to give its diol compound, which condensed with phenanthrene fused pyrrole 19 to form soluble porphyrin 41. 32 Core-modified porphyrin 42 embedded with both ITN and a phenanthrene-fused pyrrole subunit was successfully synthesized from 41 by heating at 300 1C under vacuum quantitatively. The aryl-fused thiophene and pyrrole units in 42 extended the p-conjugation of normal porphyrin and thus showed a redshifted Soret band at 543 nm and Q bands at 712 and 866 nm, making their application as near IR dyes possible.…”
Section: Porphyrinoids Embedded With Type I Building Blocksmentioning
confidence: 99%
“…To our knowledge, only porphyrins replaced with alkylselenium groups have been synthesized, but no alkylselenium phthalocyanines have been reported. 5,[11][12][13][14][15] Based on these results, further studies have been initiated to investigate the synthesis and spectroscopic properties of a novel selenium derivatized zinc(II) phthalocyanine complex to evaluate its properties as a potential photosensitizer for clinical purposes.…”
Section: Introductionmentioning
confidence: 99%